Efektivitas off the Job Training Dalam Meningkatkan Kompetensi Guru di Sekolah - Azwanda, Yuri El Hanif; Attoillah, Muhammad Farhan; Yudistira, Srikandi; Afriza, Afriza; Kodarni, Kodarni (Education Achievement: Journal of Science and Research, 2025)
Education in Indonesia faces challenges in producing human resources that are competitive in the era of globalization. This study aims to evaluate the effectiveness of off-the-job training in improving the competencies of teachers at SMA Negeri 8 Pekanbaru. The methodology used is a qualitative approach with a phenomenological case study, involving semi-structured interviews with three teachers who have participated in the training. Data were collected to understand participants' experiences, the contribution of the training to professional development, and the application of acquired skills. The results indicate that diverse training methods, such as games and simulations, are highly effective in enhancing pedagogical skills and understanding of the material. Participants reported increased student interest and engagement, as well as positive responses to the teaching methods applied. This research emphasizes the importance of continuous training to support teachers' professional development, which in turn will improve the quality of education in Indonesia.